Selective oxidation of glucose for facilitated trehalose purification. Issue 6 (June 2015) - Wu, Tsung-Ta; Ko, Ching-Chung; Chang, Shu-Wei; Lin, Sung-Chyr; Shaw, Jei-Fu
Graphical abstract: Highlights: Immobilization of glucose oxidase was investigated. Application of the immobilized oxidase in repeated-batch process was studied. The mechanism and a remedy measure for oxidase inactivation were proposed. Selective removal of gluconic acid by ion exchange was demonstrated. Abstract: To facilitate the purification of trehalose, an enzymatic process for the selective conversion of glucose was investigated. An epoxy-activated acrylic matrix was used for the immobilization of glucose oxidase. Due to the relatively hydrophobic nature of carrier surface, significant enhancement in enzyme load was observed in the presence of 1000 mM phosphate without observable enzyme denaturation. Upon immobilization glucose oxidase, with optimal activity at 40 °C and pH 7.0, was shown to have higher residual activity at elevated pHs and temperatures. In repeated-batch operations, the immobilized glucose oxidase, with a catalytic activity of 214.06 ± 5.34 U/g gel at an enzyme load of 11.31 ± 0.19 mg/g gel, exhibited sound operation stability for up to 12 cycles, beyond that the activity declined steadily, due to the sequential inactivation of catalase and glucose oxidase by the accumulated hydrogen peroxide. It was shown that the inactivation of enzymes can be alleviated by the addition of hydrogen peroxide scavengers. It was also shown that the gluconic acid thus formed can be readily adsorbed with an ion exchanger leaving trehalose in the solution. The results obtained in this study demonstrate that the proposed process could facilitate the purification of trehalose enzymatically converted from maltose.